Prevalence of mental and physical signs and symptoms among healthcare professionals at the height of Covid-19: a meta-analysis (Revista Contexto & Saúde, 2024)
Objective:  A systematic evaluation of the prevalence of mental and physical signs and symptoms among healthcare professionals who provided direct care to patients with COVID-19 at the peak of the pandemic. Method: A systematic literature review and meta-analysis, based on Joanna Briggs Institute recommendations, conducted across eleven databases. The meta-analysis considered a random-effects model. Results: Seventy-seven studies were included, totaling 31,727 healthcare professionals. Among the mental signs and symptoms, the following prevalences were identified: anxiety 56% (95% CI = 44 to 67%, p < 0.005), depression 48% (95% CI = 40 to 57%, p < 0.01), stress 60% (95% CI = 47 to 73%, p < 0.01), insomnia 54% (95% CI = 42 to 65%, p < 0.05), post-traumatic stress disorder 32% (95% CI = 20% to 46%, p < 0.01), burnout syndrome 42% (95% CI = 34% to 50%, p < 0.01). Regarding physical signs and symptoms, skin lesions related to prolonged use of personal protective equipment and higher frequency of hand washing and use of hand sanitizer prevailedl. Conclusion: Healthcare professionals who cared for patients with Coronavirus Disease 2019 at the peak of the pandemic exhibited a significant prevalence of mental and physical signs and symptoms, highlighting the need to ensure adequate health and working conditions.
Keywords: Prevalence; COVID-19; Systematic Review; Healthcare Professionals; Mental Health; Occupational Health